Functionality Investigation of the UAV Arranged FMCW Solid-State Marine Radar - Saulius Rudys; Andrius Laučys; Dainius Udris; Raimondas Pomarnacki; Domantas Bručas (Journal of Marine Science and Engineering, 2021)
Some models of marine radars are light-weight enough and thus are attractive for potential applications when arranged on UAVs. Elevating a marine radar to high altitudes provides a much wider field of view, however, this could lead to a higher radio interference level. The practical estimation of the radio interferences affecting the solid-state FMCW marine radar at altitudes up to 120 m was the main objective of this contribution. A rotary-wing octocopter UAV was developed and built for the experiments. Two different kinds of interferences were observed at higher altitudes. Ray-like interferences were caused by signals, which are received by the radar’s antenna. Circle-like interferences appear due to the low frequency interfering signal directly penetrating the detector due to insufficient receiver screening.